Outcome of ventilatory support for acute respiratory failure in motor neurone disease. Issue 6 (1st June 2002) - Bradley, M D; Orrell, R W; Clarke, J; Davidson, A C; Williams, A J; Kullmann, D M; Hirsch, N; Howard, R S
Abstract : Objectives: To review the outcome of acute ventilatory support in patients presenting acutely with respiratory failure, either with an established diagnosis of motor neurone disease (MND) or with a clinical event where the diagnosis of MND has not yet been established. Methods: Outcome was reviewed in 24 patients with respiratory failure due to MND who received endotracheal intubation and intermittent positive pressure ventilation either at presentation or as a result of the unexpected development of respiratory failure. Patients presenting to local hospitals with acute respiratory insufficiency and requiring tracheal intubation, ventilatory support, and admission to an intensive therapy unit (ITU) before transfer to a regional respiratory care unit were selected. Clinical features of presentation, management, and outcome were studied. Results: 24 patients with MND were identified, all being intubated and ventilated acutely within hours of presentation. 17 patients (71%) were admitted in respiratory failure before the diagnosis of MND had been made; the remaining seven patients (29%) were already known to have MND but deteriorated rapidly such that intubation and ventilation were initiated acutely. Seven patients (29%) died on ITU (between seven and 54 days after admission). 17 patients (71%) were discharged from ITU. 16 patients (67%) received long term respiratory support and one patient required no respiratory support following tracheal extubation. The daily duration of support that was required increased gradually with time. Conclusion: When a patient with MND is ventilated acutely, with or without an established diagnosis, independence from the ventilator is rarely achieved. Almost all of these patients need long term ventilatory support and the degree of respiratory support increases with time as the disease progresses. The aim of management should be weaning the patient to the minimum support compatible with symptomatic relief and comfort. Respiratory failure should be anticipated in patients with MND when the diagnosis has been established.